2021
DOI: 10.1016/j.jth.2021.101061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on air quality and pollution in different countries

Abstract: Introduction COVID-19 is a pandemic that affected humans’ lives and activities through the year 2020 in a way that was not witnessed in recent years. Many governments declared a complete lockdown as a try to stop the transmission of the disease. This lockdown resulted in a good recovery in environmental health, where air pollutants levels dramatically decreased. Theory There are two relations between air pollution and COVID-19, one is before the disease spread, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…In response to the threats of the COVID-19 spread, countries have been taking measures, including social distancing, lockdown, and quarantines. Resultantly, it has abruptly affected the individual's mobility patterns around the world ( Albayati et al, 2021 ; Hensher, 2020 ; Shamshiripour et al, 2020 ). Although the vaccines are available now in some countries and they are expected to control the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the threats of the COVID-19 spread, countries have been taking measures, including social distancing, lockdown, and quarantines. Resultantly, it has abruptly affected the individual's mobility patterns around the world ( Albayati et al, 2021 ; Hensher, 2020 ; Shamshiripour et al, 2020 ). Although the vaccines are available now in some countries and they are expected to control the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists that NO 2 has negative environmental-human health consequences, especially in circumstances where prolonged exposure is experienced [75]. Nitrogen oxides are mainly produced by anthropogenic activities, including vehicular emissions, biomass burning, fossil fuel combustion, thermal power plants, domestic solid fuel use, while natural sources include lightning and soils [76][77][78]. Matandirotya and Burger [79] found that seasonal biomass burning, which increased during the winter season, was also related to the emission of nitrogen oxides.…”
Section: Resultsmentioning
confidence: 99%
“…20 The ACE-2 is existing in different organs cells, such as the epithelial cells of the lung alveolar, small intestine enterocytes, and smooth muscle cells. 21 The ACE-2 is also found in cardiomyocytes cells, cardiac fibroblasts, and coronary endothelial cells in heart failure cases. 22,23 It is good to mention that the ACE-2 is higher in healthy, renal disease, and diabetic men compared with women.…”
Section: Death Casesmentioning
confidence: 99%